Influence of solvent on branching via atom transfer radical polymerisation using 1, 6-bismaleimidohexane as branching agent. (June 2014) - Huang, W. Y.; Xue, X. Q.; Zhang, D. L.; Chen, J. H.; Fang, J. B.; Yang, H. J.; Jiang, B. B.; Kong, L. Z.; Liu, Y.; Pu, H. T.
Abstract : Branched polystyrenes have been prepared via atom transfer radical polymerisation using 1, 6-bismaleimidohexane as the branching agent in two reaction systems of anisole or anisole along with N -methyl pyrrolidone (NMP). The polymerisation kinetics was studied using gas chromatography. The formation mechanism, the development of branching, the changes in molecular weight and polydispersity of branched polymers were analysed using triple detection size exclusion chromatography. The results showed that the formation mechanisms of branched polystyrenes were almost the same in both the reaction systems. The relative molecular weights were also similar at the same conversion of styrene in the two reaction systems because of similar contents of the pendent vinyl groups between the two reaction systems. However, higher absolute molecular weight and higher branching degree of the branched chains were obtained in the anisole with NMP than that in the anisole alone at the same styrene conversion.